Tariff Liberalization and Trade Specialization in India - Michele Alessandrini; Bassam Fattouh; Benno Ferrarini; Pasquale Scaramozzino (Asian Development Bank (ADB), 2009)
Since the early 1990s, India has embarked on economic reforms that have progressively opened up the country to international trade. This paper analyzes the effects of reform on India's trading structure from 1990 to 2006. It computes comparative advantage indicators on the basis of disaggregated trade flow data, and assesses the effects of trade liberalization on the evolution of India's pattern of trade specialization. From dynamic panel regression analysis, evidence is found that those industries where import tariffs have been reduced the most have experienced the highest increase in specialization. Moreover, the analysis shows that trade liberalization has helped India improve its comparative advantage in industries with medium- to high-technology content, as well as in some of the industries enjoying the most robust growth in global demand.
hdl:11540/1837
Keywords: 330